Al-SiC Metal Matrix Composite production through Friction Stir Extrusion of aluminum chips. (2017) - Baffari, Dario; Buffa, Gianluca; Campanella, Davide; Fratini, Livan
Abstract: The production of most mechanical component requires machining operation, thus usually implying the cut material to be wasted as scrap. Traditional recycling techniques are not able to efficiently recycle metal chips because of some critical aspects that characterize such kind of scraps (shape, oxide layers, contaminating residues, etc). Friction Stir Extrusion is an innovative solid state direct-recycling technique for metal machining chips. During the process, a rotating tool is plunged into a hollows matrix to compact, stir and finally, back extrudes the chips to be recycled in a full dense rod. This process results to be particularly relevant since no preliminary treatment of the scrap is required. Experimental campaigns have been carried out in order to investigate the effects on process mechanics of the introduction of silicon carbide micro powders.